Development and validation of suicide crisis scale for international students in South Korea - Choi, Ki-Hyun; Ha, Jung Hee; Jue, Juliet (Frontiers in Psychology, 2024)
This study created and validated a scale to measure the level of suicide crisis among international students attending South Korean universities. Study 1 developed questions and constructed the components of the scale using an initial survey of 248 people and exploratory factor analysis. Study 2 validated the scale using a second survey of 340 participants and confirmatory factor analysis. The results showed that 21 items were confirmed in six factors, which include lack of social support, burdensomeness, maladaptation to Korean culture, academic maladjustment, suicidal thoughts, and suicide risk. We verified the convergent validity, criterion validity, and reliability of the scale. The significance and implications of this study are presented, along with suggestions for future research.